Organosolv Pretreatment of Sugar Cane Bagasse for Bioethanol Production - Terán Hilares R. (2017)
The authors gratefully acknowledge the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC/CIENCIACTIVA-Peru, Process number 219-2014) and Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPqBrazil, process number 449609/2014-6).